Advancing theory for kinetics and dynamics of complex, many-dimensional systems : clusters and proteins - Komatsuzaki, Tamiki; Berry, R. Stephen, 1931-2020; Leitner, David M., 1963- (Advances in chemical physics ;, 2011)
This series provides the chemical physics field with a forum for critical, authoritative evaluations of advances in every area of the discipline. Volume 145 in the series continues to report recent advances with significant, up-to-date chapters by internationally recognized researchers.